Вплив холоду на периферичний кровообіг у осіб різних соматотипів із нормальним та підвищеним артеріальним тиском - Vadzyuk , Stepan; Horban, Liudmyla; Papinko, Ihor; Kulianda, Olena (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2020)
Abstract: The peculiarities of peripheral blood flow response during cold test in young people of different somatotypes with normal and high blood pressure have been studied. Among the vast majority of subjects, a negative cold test was found in the people with normal blood pressure, that testified to a normal vascular response to cold effect. In the persons with high blood pressure, the percentage of cases with negative cold test was significantly lower. The vascular bed response to cold effect in people with high blood pressure and endomorphic body type was distinguished by the spastic process development. The cold test results showed the hypotonic responses to be typical for people with a predominant ectomorphic share of somatotype and high blood pressure, and a mixed type of responses as common for those with mesomorphic body type and high blood pressure. Probl Cryobiol Cryomed 2020; 30(3): 270–279